The Cambridge economic history of modern Britain - Floud, Roderick; Humphries, Jane 1948-; Johnson, Paul (Paul A.) (Cambridge, United Kingdom Cambridge University Press, 2014)
"A new edition of the leading textbook on the economic history of Britain since industrialisation. Leading historians and economists examine the foundational importance of economic life in modern Britain as well as the close interconnections between economic, social, political and cultural change. Each chapter provides a clear guide to the major controversies in the field and students are shown how to connect historical evidence with economic theory and how to apply quantitative methods. Volume 1, on 1700-1870, offers new approaches to classic issues such as the causes and consequences of industrialisation, the role of institutions and the state, and the transition from an organic to an inorganic economy, as well as introducing new issues such as globalisation, convergence and divergence, the role of science, technology and invention, and the growth of consumerism. Throughout the volume, British experience is set within an international context and its performance benchmarked against its global competitors"--Provided by publisher.
v. II. 1870 to the present. The legacy of the early start / Knick Harley -- Economic growth during the long twentieth century / Nicholas Crafts -- From empire to Europe : Britain in the world economy / Kevin Hjortshof O'Rourke -- Population, migration and labour supply : Great Britain 1871-2011 / Timothy J. Hatton -- Health and welfare / Bernard Harris -- Income and living standards, 1870-2010 / Ian Gazeley -- Technology, innovation and economic growth in Britain since 1870 / Tom Nicholas -- Consumption and affluence, c. 1870-2010 / Avner Offer -- Cycles and depressions / Matthias Morys -- The city and the corporate economy since 1870 / David Chambers -- Armaments and the economy / Jari Eloranta -- The de-industrial revolution : the rise and fall of UK manufacturing, 1870-2010 / Michael Kitson and Jonathan Michie -- The rise of the service sector / Stephen Broadberry -- The household economy since 1870 / Peter Scott -- The growth of the public sector / Robert Millward -- Soft power : the media industries in Britain since 1870 / Gerben Bakker -- Sterling and monetary policy, 1870-2010 / Catherine R. Schenk -- Economic policy and management / Roger Middleton -- Economic thought and ideology in Britain, 1870-2010 / Roger E. Backhouse and Keith Tribe.
Includes bibliographical references and index.
Keywords: Great Britain -- Economic conditions; Great Britain -- Economic conditions -- 18th century; Great Britain -- Economic conditions -- 19th century; Great Britain -- Economic conditions -- 20th century